Retraction notice: Daily versus post-dialysis administration of calcimimetics for the treatment of secondary hyperparathyroidism in haemodialysis patients: an interventional, multi-centre study - Editors, The (African Journal of Nephrology, 2020)
The authors of this paper [1] contacted the Journal on 1 May 2020, shortly after its publication on 25 April 2020, and requested that it be retracted because of the following reasons: - the authors did not have permission from the dialysis provider company to publish the data - some data were from different time frames and the related results are therefore inaccurate - consent was not obtained from all patients - some co-authors who should have been included, were not. The editors of the Journal, after consultation with senior members of the editorial board, have decided that the article be retracted and that the relevant institutions and ethics committee be informed. The metadata of the article has been amended to indicate the retraction and the PDF version of the paper, which will remain on the Journal website, now has a watermark indicating “RETRACTED”. Reference 1. Demerdash TM, Abdelsalam M, Assem M, Shaheen MM, Marie MA. Daily versus post-dialysis administration of calcimimetics for the treatment of secondary hyperparathyroidism in haemodialysis patients: an interventional, multi-centre study. Afr J Nephrol. 2020; 23(1):81-84.